Evaluation of the Implementation of the Merdeka Belajar Curriculum in Secondary Schools in the Digital Era - Husnul Haq; Wakidi (Yayasan Azhar Amanaa Yogyakarta, 2024)
This study evaluates the implementation of the Merdeka Belajar Curriculum in Indonesian secondary schools within the digital era. The curriculum aims to foster a flexible, student-centered education to enhance creativity, independence, and adaptability among students. Utilizing qualitative methods, including interviews, observations, and document analysis, the research explores the curriculum's impact on teaching practices and learning outcomes. The findings indicate that the curriculum has effectively introduced project-based learning and digital tools, creating a more engaging and interactive classroom environment. Students have demonstrated improved academic performance and growth in essential soft skills such as communication and collaboration. However, challenges persist, including disparities in digital infrastructure between urban and rural areas and varying levels of digital readiness among teachers. Teacher feedback highlights positive aspects of the curriculum but also points to the need for more professional development and support. Students appreciate the curriculum's relevance but suggest improvements in assessment guidelines and feedback mechanisms.